1993
DOI: 10.1103/physrevd.47.5357
|View full text |Cite
|
Sign up to set email alerts
|

Naked singularities in spherically symmetric inhomogeneous Tolman-Bondi dust cloud collapse

Abstract: We investigate here the occurrence and nature of naked singularity for the inhomogeneous gravitational collapse of Tolman-Bondi dust clouds. It is shown that the naked singularities form at the center of the collapsing cloud in a wide class of collapse models which includes the earlier cases considered by Eardley and Smarr [5] and Christodoulou [6]. This class also contains self-similar as well as non-self-similar models. The structure and strength of this singularity is examined and the question is investigat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
397
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(411 citation statements)
references
References 32 publications
(38 reference statements)
13
397
0
1
Order By: Relevance
“…Detailed analysis on the occurrence of naked shell-focusing singularity has been done in [1][2][3][4][29][30][31]. Here we present one of the results.…”
Section: Lemaître-tolman-bondi Solutionmentioning
confidence: 65%
See 1 more Smart Citation
“…Detailed analysis on the occurrence of naked shell-focusing singularity has been done in [1][2][3][4][29][30][31]. Here we present one of the results.…”
Section: Lemaître-tolman-bondi Solutionmentioning
confidence: 65%
“…It was shown that the collapse of an inhomogeneous dust ball results in shell-focusing naked singularity formation [1][2][3][4]. Ori and Piran [5][6][7] and Harada [8] showed that naked singularity formation is possible from the spherical collapse of a perfect fluid with a very soft equation of state.…”
Section: Introductionmentioning
confidence: 99%
“…This causes the shrinkage of the collapsing object due to the radiation of high energy matter fluxes. Such effects are claimed to result from the formation of naked singularities [13]. These secondary effects and similar ones are considered to provide probable empirical evidences for the indirect proof of some quantum gravity theories [1].…”
Section: Jhep02(2017)124mentioning
confidence: 99%
“…Gravitational collapse is well studied analytically and numerically, in the framework of General Relativity [6,7,8,9,10,11], and modifications of GR as well [12,13,14,15,16,17]. The exact solution of Einsteins' field equations play a crucial role in understanding a collapsing solution in a detailed manner.…”
Section: Introductionmentioning
confidence: 99%